Relação peso-comprimento para 22 espécies de peixes do Reservatório de Salto Santiago, Rio Iguaçu, Paraná - Horlando, Solange da Silva (2012)
In this study, we analyzed the length-weight relationship of 22 fish species Reservoir Salto Santiago, Rio Iguaçu, Paraná. For 10 of the species studied, was pronounced sexual dimorphism in weight-length relationships, where fêrmeas grew more than males, due to their greater investment in reproduction. For 12 of the remaining species did not differ between sexes (the ANCOVA was not significant), so a relationship was present only for the species, encompassing both sexes, there was no difference in allometric growth between males and females. The value of b for 15 species was greater than 3, indicating a higher investment than in wt growth. As for seven species the value of b was less than 3, indicating a greater increase in growth by weight.